The Impact of the Pre-Employment Card Program on Job Search Duration in Semarang City - Priscilia, Risky; Yulia Purwanti, Evi (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
Unemployment issues arise due to an imbalance between the labor force and available job opportunities, as well as a mismatch of skills. This situation prompted the government to introduce the Pre-Employment Card Program, aimed at enhancing skills through job training and incentives. This study seeks to analyze the influence of variables such as training programs and incentives under the Pre-Employment Card Program, educational level, work experience, reservation wage, age, and gender on the duration of job searching in Semarang City. The research adopts a quantitative approach, focusing on respondents who have participated in the Pre-Employment Card Program in Semarang City. The analytical method employed is multiple linear regression analysis (Ordinary Least Squares). The findings indicate that the training programs and incentives from the Pre-Employment Card Program, educational level, and reservation wage have a significant impact on the duration of job searching in Semarang City. Conversely, work experience, age, and gender do not significantly influence the job search duration. The independent variables collectively explain 43.32% of the variation in job search duration, while the remaining 56.68% is attributed to other variables outside the research model.